Planetary Protection in the New Space Era: Science and Governance - Cheney, Thomas; Newman, Christopher; Olsson-Francis, Karen; Steele, Scott; Pearson, Victoria; Lee, Simon (Frontiers in Astronomy and Space Sciences, 2020)
COSPAR’s Planetary Protection Policy is a triumph of technocratic governance in the global sphere. The Policy is produced by a group of scientific experts and subsequently enjoys high regard among the scientific and space community. However, as COSPAR is an independent organization without any legal mandate the Planetary Protection Policy is an example of so-called ‘soft law’ or a non-binding international instrument, in short, no one is under any legal obligation to comply with them. The policy is linked to Article IX of the Outer Space Treaty and its provision calling for the avoidance of ‘harmful contamination’ of the Moon and other celestial bodies. While space activities beyond Earth orbit have been the exclusive preserve of government scientific space agencies this has posed little problem. However as private and ‘non-science’ space activities proliferate and begin to spread their reach beyond Earth orbit, the Planetary Protection Policy is being tested. This paper will examine the challenges of developing and maintaining an effective planetary protection regime in this ‘New Space’ era. This will involve looking at the existing policies, as well as the governance framework they sit within. However, it is also necessary to consider and understand the scientific basis not just for the specifics of the policy itself but the necessity of it. Finally, this paper will consider whether a broader ‘environmental’ framework is needed as space activities diversity in type and location.